Peacefully Demobilizing Rebels: Identity, Emotional Cues, and the FARC - Juan P. Aparicio; Michael Jetter; Christopher Parsons (Institute of Labor Economics (IZA), 2023)
In the early 2000s, the Colombian government aired messages during games of the national football team, urging FARC rebels to demobilize. We first study the strategy's effectiveness, leveraging game dates, kick-off times, and spatial-temporal variation in rain-induced signal strength in a municipality-day-level panel spanning 2003-2016. Over 1,000 rebels demobilized because of family-themed (but not national-unity-themed) messages, received during unexpected losses (i.e., negative emotional cues). We then model a rebel's demobilization decision, combining identity salience with their emotional state. Finally, we corroborate the model's predictions examining family- versus non-family-specific holidays and local climatic anomalies.
Keywords: D74; D91; H56; L82; N46; O54; 330; civil war; conflict resolution; demobilization; hearts-and-minds; information campaigns